O ethos discursivo como gestão da autoria: análise do objeto editorial Turma da Mônica: Romeu e Julieta (2015) - Slompo, Ana Paula (Universidade Federal de São Carlos, 2022)
Based on reflections on the marketing aspect of the literary field and the concept of literary space (MAINGUENEAU, 2018), we analyzed the position of the editorial object Turma da Mônica: Romeu e Julieta (2015). For this purpose, we used the concepts of medium (DEBRAY, 2000) and discursive ethos (MAINGUENEAU, 2008) within the framework of Materialist Discourse Analysis. This editorial object is an adaptation (HUTCHEON, 2011) of a well-known story with other well-known characters, which is why we use the concept of ethos for the analysis: we want to know what Monica's Gang remains in the recount of Romeo and Juliet. Furthermore, we mobilized the concept of material formalization developed by Flusser (2007), the notion of intermediality (CLUVER, 2006), and approaches to the symbology of colors from the study of Guimarães (2001). We used these concepts because the object raises several questions about the literary field, especially the publication of adaptations in comics, because of its material existence and its position in the field, as Turma da Mônica: Romeu e Julieta (2015) is an adaptation of Shakespeare's classic play Romeo and Juliet, which was very successful in different parts of the world and at various times in history, being released in the 20th century in Brazil, both in the form of a comic book (1978) and as theater (1978), film (1979) and LP (1978). We studied the 2015 edition when the comic had a reissue commemorating the 80th anniversary of the creator of the characters of Monica's Gang and author of many stories involving the gang, Mauricio de Sousa, which led us to think about authorship from the proposals of Maingueneau (2018). With the analysis, we understood how the discursive ethos acts in adaptations such as this: the effective ethos of this composition of Monica's Gang and Romeo and Juliet is paratopic, as is the text's authorship.
Discourse ethos as management of authorship: analysis of the editorial object Turma da Mônica: Romeu e Julieta (2015)
Keywords: Autoria; Adaptação; Ethos Discursivo; Histórias em Quadrinhos; Authorship; Adaptation; Discursive Ethos; Comic Books; LINGUISTICA, LETRAS E ARTES::LINGUISTICA